The social work and human services workforce : report from a national study of education, training and workforce needs. - Healy, Karen; Lonne, Bob (Australian Learning and Teaching Council, 2010)
This report analyses the national curriculum and workforce needs of the social work and human services workforce. Australia's community and health services are among the fastest growing sectors of employment in the nation but the sustainability of an appropriately qualified workforce is threatened. Yet there is little integration of education and workforce planning for the community services sector. This contrasts markedly with the health services sector, where key stakeholders are collaboratively addressing workforce challenges. Our research confirmed rapid growth in the social work and human services workforce. Our study revealed a lack of co-ordination across VET and higher education to meet the educational needs of the social work and human services workforce. The recommendations given were to identify courses as a national priority, VET and education providers are encouraged to develop accessible pathways, DEEWR to undertake a national workforce analysis and COAG to develop a national framework. [Executive summary, ed]